Active Learning in Fluid Mechanics: Low Cost Hands on Activities for Understanding of Valve Types - Nauli, Maria Anindita (Universitas Negeri Semarang, 2025)
Background - Creative thinking skills are an important ability in 21st century learning, especially in mathematics as part of higher order thinking skills. Purpose - This study aims to analyze the effect of Problem Based Learning (PBL) on aspects of students' mathematical creative thinking skills, namely fluency, flexibility, originality, and elaboration. Method/approach - This quantitative research used a quasi-experimental approach with a pretest-posttest control group design which was carried out for 1 month. The sample consisted of 32 students of class VIII-10 and 31 students of class VIII-11 of SMPN 1 Bandar Lampung who were selected by purposive sampling. Findings - The Mann Whitney U Test results showed that students who learned with PBL experienced a more significant increase in mathematical creative thinking skills than students who learned conventionally, especially in certain aspects. The application of PBL not only improves creativity in general but also strengthens the originality and flexibility of students' thinking in mathematical problem solving. The strength of this study lies in the in-depth analysis of the effect of PBL on specific aspects of mathematical creativity, not just the overall improvement. Conclusions - This study also provides empirical evidence of the effectiveness of PBL in improving higher order thinking skills at the junior high school level. Novelty/Originality/Value - Thus, PBL is proven to have an effect on students' mathematical creative thinking skills.